2012
DOI: 10.1371/journal.pone.0045223
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium Derived Factor Inhibits the Growth of Human Endometrial Implants in Nude Mice and of Ovarian Endometriotic Stromal Cells In Vitro

Abstract: Angiogenesis is a prerequisite for the formation and development of endometriosis. Pigment epithelium derived factor (PEDF) is a natural inhibitor of angiogenesis. We previously demonstrated a reduction of PEDF in the peritoneal fluid, serum and endometriotic lesions from women with endometriosis compared with women without endometriosis. Here, we aim to investigate the inhibitory effect of PEDF on human endometriotic cells in vivo and in vitro. We found that PEDF markedly inhibited the growth of human endomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Isolation of primary human endometrial epithelial cells was undertaken as described in our previous paper 37 . Then, cells were cultured in Dulbecco's Modified Eagle's medium: Nutrient Mixture F‐12 (DMEM/F 12; Keyi Biotechnology) containing penicillin (50 U/mL), streptomycin (50 μg/mL) and foetal bovine serum (FBS; 12% (v/v)), all of which were from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of primary human endometrial epithelial cells was undertaken as described in our previous paper 37 . Then, cells were cultured in Dulbecco's Modified Eagle's medium: Nutrient Mixture F‐12 (DMEM/F 12; Keyi Biotechnology) containing penicillin (50 U/mL), streptomycin (50 μg/mL) and foetal bovine serum (FBS; 12% (v/v)), all of which were from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of primary human endometrial epithelial cells was undertaken as described in our previous paper. 37 Then, cells were cul-…”
Section: Culture Of Human Endometrial Cells and Interventionmentioning
confidence: 99%
“…The mice were tested for drug distribution 10 days after surgery. 23,31 The rats were anesthetized before making a vertical incision on the abdomen. The distal 1 cm segment of the uterine horn was extracted and immediately placed in sterile saline.…”
Section: In Vitro Cytotoxicity Studiesmentioning
confidence: 99%
“…We (Chuderland et al 2013c) and others (Chen et al 2011 have recently suggested the use of PEDF for treating endometriosis. Sun et al (2012) showed that PEDF gene treatment inhibits the growth of human endometriotic cells in vivo when transplanted to a nude mouse model; they have further showed that this treatment reduces VEGF level and angiogenesis in the lesion . We showed that treatment with rPEDF eradicates endometrial lesions as well as causes a significant decrease in the level of VEGF in the lesions.…”
Section: The Role Of Pedf In Endometrial Physiology and Pathologymentioning
confidence: 96%